High rate of in-stent restenosis after coronary intervention in carriers of the mutant mannose-binding lectin allele - Bagyura, Zsolt; Hirschberg, Kristóf (BMC cardiovascular disorders, 2017)
In-stent restenosis occurs in 10-30% of patients following bare metal stent (BMS) implantation and has various risk factors. Mannose-binding lectin (MBL) is known to have effect on the progression of atherosclerosis. Single nucleotide polymorphisms (SNP) of the MBL2 gene intron 1 (codon 52, 54, 57) are known to modulate the bioavailability of the MBL protein. Our aim was to identify the association of these polymorphisms of the MBL gene in the occurrence of in-stent restenosis after coronary artery bare metal stent implantation.